Recent Progresses in the Design and Fabrication of Highly Efficient Ni-Based Catalysts With Advanced Catalytic Activity and Enhanced Anti-coke Performance Toward CO2 Reforming of Methane - Wu, Xianyun; Xu, Leilei; Chen, Mindong; Lv, Chufei; Wen, Xueying; Cui, Yan; Wu, Cai-e; Yang, Bo; Miao, Zhichao; Hu, Xun (Frontiers in Chemistry, 2020)
CO2 dry reforming of methane (CRM) can effectively convert two greenhouse gases (CO2 and CH4) into the syngas (CO + H2). This process can achieve the efficient resource utilization of CO2 and CH4 and reduce environmental greenhouse gases. Therefore, the CRM has been considered as a significantly promising route for sustainable development. Ni-based catalysts have been widely investigated in CRM reactions due to their various advantages, such as the high catalytic activity, low price, and abundant reserves. However, the Ni based catalysts usually suffer from rapid deactivation because of the thermal sintering of the metallic Ni active sites and surface coke deposition, which restricted the industrialization of the Ni based catalysts toward CRM process. In order to address these challenges, the worldwide scientists have devoted great efforts to investigating various influencing factors, such as the option of the appropriate supports and promoters, the construction of strong metal-support interaction, etc. Therefore, we carefully summarized the recent development in the design and preparation of Ni-based catalysts with advanced catalytic activity and enhanced anti-coke performance toward CRM reactions in this review. Specifically, the recent progresses of the Ni-based catalysts with different supports, additives, preparation methods, and so on, have been summarized in detail. Furthermore, the recent development of the reaction mechanism studies over the Ni-based catalysts were also covered by this review. Finally, the future development trend of the high-efficient Ni-based catalyst with excellent anti-coke performance was prospected.